The influence of 7-OH methotrexate metabolite on clinical relevance of methotrexate determination - Klapkova, Eva; Kukacka, Jiri; Kotaska, Karel; Suchanska, Iveta; Urinovska, Romana; Prusa, Richard (Clinical laboratory, 2011)
BACKGROUND: A modified high performance liquid chromatographic (HPLC) method has been developed for the simultaneous determination of methotrexate (MTX) and its main metabolite 7-hydroxymethotrexate (7-OHMTX) and compared to the immunochemical fluorescence polarization immunoassay (FPIA2) determination of methotrexate. METHODS: Methotrexate was determined by HPLC with UV detection at 303 nm after precipitation of proteins with trichloroacetic acid. Fluorescence polarization immunoassays (FPIA2) of methotrexate were performed on the TDx FLx Immunoassay Analyzer. RESULTS: Our data indicate good correlation between methotrexate levels > 1 micromol/L determined by HPLC and FPIA2. (r = 0.94, Spearman correlation coefficient). However, concentrations of methotrexate < 1 micromol/L measured by fluorescence polarization immunoassay were overestimated. CONCLUSIONS: The concentration of MTX < 1 micromol/L are overestimated due to the cross reactivity with metabolites 7-OHMTX and 2,4-diamino-N10-methylpteroic acid (DAMPA). The cross reaction may affect the therapy and lead to relapse in children with acute lymphoblastic leukemia.
Keywords: Chromatography, High Pressure Liquid; Drug Monitoring; Biotransformation; osteosarkom; Humans; nádory kostí; methotrexát; Antimetabolites, Antineoplastic; dítě; monitorování léčiv; Child; Bone Neoplasms; mladý dospělý; Methotrexate; Osteosarcoma; lidé; fluorescenční polarizační imunologické testy; Adolescent; protinádorové antimetabolity; Fluorescence Polarization Immunoassay; Young Adult; biotransformace; akutní lymfatická leukemie; Precursor Cell Lymphoblastic Leukemia-Lymphoma; vysokoúčinná kapalinová chromatografie; mladiství